Analisis Terhadap Disparitas Antar Wilayah dan Pertumbuhan Ekonomi di Sulawesi Selatan - Hukma Ratu Purnama; Andika Pramukti Lamo; Ade Putri Lestari; Putri Fidyah Majid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines economic growth and regional disparities in South Sulawesi Province during the 2019–2023 period, focusing on the development of the Human Development Index (HDI). The urgency of this research lies in understanding the factors influencing HDI growth as a primary indicator of societal welfare and quality of life, particularly in efforts to reduce regional disparities. This study employs a descriptive quantitative method, analyzing secondary data obtained from official publications such as the Central Bureau of Statistics and related agencies, to assess HDI growth trends and compare them with the national average. The findings reveal that South Sulawesi’s HDI has steadily increased from 73.08 in 2020 to 74.60 in 2023. Generally, the province’s HDI achievement is slightly above the national average, which rose from 72.81 in 2020 to 74.39 in 2023. Since 2017, South Sulawesi's human development status has been classified as "high," ranging between 70 and 80. Over the past four years, HDI growth has been within the 0–1 percent range, with significant acceleration in the last two years. In 2021, HDI grew by 0.41 percent, followed by faster growth of 0.79 percent in 2022, and reaching 0.87 percent in 2023, with an increase of 0.64 points compared to the previous year.